Report of the FAO Regional Workshop on the Elaboration of National Plans of Action to Prevent, deter and eliminate illegal, unreported and unregulated fishing, Pacific Islands subregion : (Food and Agirculture Organization of the United Nations, 2005)
A report of the FAO regional workshop on the elaboration of national plans of action to prevent, deter and eliminate illegal, unreported and unregulated fishing in the Pacific islands subregion.